Approximation and Online Algorithms 8th International Workshop, WAOA 2010, Liverpool, UK, September 9-10, 2010. Revised Papers - Jansen, Klaus; Solis-Oba, Roberto (Springer eBooks., 2011)
This book constitutes the thoroughly refereed post workshop proceedings of the 8th International Workshop on Approximation and Online Algorithms, WAOA 2010, held in Liverpool, UK, in September 2010 as part of the ALGO 2010 conference event. The 23 revised full papers presented were carefully reviewed and selected from 58 submissions. The workshop covered areas such as algorithmic game theory, approximation classes, coloring and partitioning, competitive analysis, computational finance, cuts and connectivity, geometric problems, inapproximability results, mechanism design, network design, packing and covering, paradigms for design and analysis of approximation and online algorithms, parameterized complexity, randomization techniques, real-world applications, and scheduling problems.